Service Quality To Customer Loyalty Through Indihome Cutomer Value In West Bandung - Widjojo, Rosita; Khotimah, Khusnul; Zakaria, Zakaria (Universitas Yapis Papua, 2023)
The purpose of this study was to determine whether there is a relationship between service quality on customer loyalty and customer value as a mediating variable. The research method is quantifiable and qualitative with the type of associative research. The population in the study was all customers of indihome west bandung regency which amounted to 872 people. The sample numbered 130 people taken with slovin formula, with purposive sampling is sampling technique type accidental sampling. Tools in this study using Amos 25 and supported by sobel test. The result shows an indirect relationship of 0,970 > direct 0,076, and the sobel test result of the Z value is 4,77353 > dari 1,65694. This means that there is a relationship between service quality to customer loyalty through Indihome Customer Value in West Bandung